Proceedings of the 14th ACM / IEEE International Symposium on Empirical Software Engineering and Measurement (ESEM) 2020
DOI: 10.1145/3382494.3421462
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Agile Test Artifacts Useful?

Abstract: Background: The artifacts used in Agile software testing and the reasons why these artifacts are used are fairly well-understood. However, empirical research on how Agile test artifacts are eventually designed in practice and which quality factors make them useful for software testing remains sparse. Aims: Our objective is twofold. First, we identify current challenges in using test artifacts to understand why certain quality factors are considered good or bad. Second, we build an Activity-Based Artifact Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Whereas Fischbach et al [23] identified 16 quality characteristics for six Agile test artifacts, they focused on the Agile test artifacts in general. They proposed only one quality characteristic of the unit TCs: the code coverage, which is insufficient to measure TCQ.…”
Section: A Test Case Quality Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas Fischbach et al [23] identified 16 quality characteristics for six Agile test artifacts, they focused on the Agile test artifacts in general. They proposed only one quality characteristic of the unit TCs: the code coverage, which is insufficient to measure TCQ.…”
Section: A Test Case Quality Modelsmentioning
confidence: 99%
“…1 above, it is clear that most studies presented the TCQ from a traditional approach. Four studies [15], [23], [41], [49] tried to improve the testing quality in the ASD method. Nevertheless, the majority did not define sub-characteristics; only one study proposed characteristics, sub-characteristics, and metrics developed by Lai [15].…”
Section: A Test Case Quality Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contudo, os autores reforçam a necessidade de refinar os achados voltando aos participantes da pesquisa para validar na prática quão úteis são os novos atributos de qualidade e a lista de verificação baseada em perguntas para que possam ser usados em contextos BDD no mundo real e obter resultados confiáveis. O estudo de [8] buscou identificar os desafios atuais no uso de artefatos de teste para entender por que certos fatores de qualidade são considerados bons ou ruins. Além disso, elaboraram um modelo de qualidade de artefato baseado em atividade que descreve como os artefatos de teste ágeis devem ser.…”
Section: Trabalhos Correlatosunclassified
“…User stories can also be used as the basis for test cases in software testing processes [8]- [10]. Acceptance criteria assigned to user stories are used as test cases and merged into acceptance tests, which will then be used to check the system behavior compliance with the user stories [11].…”
Section: Introductionmentioning
confidence: 99%